Temporal trends in peripheral arterial interventions: Observations from the blue cross blue shield of michigan cardiovascular consortium (BMC2 PVI). Issue 4 (27th February 2017) - Thomas, Michael P.; Jung Park, Yeo; Grey, Scott; Schreiber, Theodore L.; Gurm, Hitinder S.; Leffler, Dale; Davis, Thomas P.; Henke, Peter; Michael Grossman, Paul
Abstract : Objectives: The aim is to examine trends in procedural indication, arterial beds treated, and device usage in peripheral arterial interventions (PVIs). Background: There is little data on indication, vascular beds treated and devices utilized for peripheral arterial interventions. Methods: We used data from 43 hospitals participating in the BMC2 VIC registry. PVIs were separated by year and divided by arterial segment. Lower extremity PVIs were subclassified as having been performed for claudication or critical limb ischemia (CLI). Yearly device usage was also included. A repeated measure ANOVA was used to determine trends. Results: 44, 650 PVIs were performed from 2006 to 2013. Renal interventions decreased from 18% of interventions in 2006 to 5.6% in 2013 ( P  < 0.001) and femoral‐popliteal increased from 54.9% in 2006 to 64.5% in 2013 ( P  < 0.001). No significant trend was seen for aorta‐iliac or below‐the‐knee interventions. 58.6% of PVIs were performed for claudication in 2006 and this decreased to 44.6% in 2013 ( P  = 0.025). Indications for CLI were 24.1% in 2006 and 47.5% in 2013 ( P  < 0.001). There were significant increases in the use of balloon angioplasty ( P  = 0.029) and cutting/scoring balloons ( P  < 0.001) while cryoballoon usage decreased ( P  < 0.001). No significant changes were found with stenting, atherectomy, and laser. Conclusions: There is a significant increase in patients presenting with CLI. Renal artery intervention rates are decreasing while femoral‐popliteal interventions are increasing. Additionally, balloon angioplasty and cutting/scoring balloon usage is increasing. © 2017 Wiley Periodicals, Inc.